Peningkatan Efisiensi Peternakan Sapi Potong Melalui Manajemen Terstruktur Bagi Peternak Penerima Kredit Program Paronisasi Koperasi Solidaritas - Krova, Maria; Kleden, Markus M. Kleden; Sembiring, Sabarta; Sulistidjo, Edi Djoko; Lalus, Matheos F.; Lano, Marten Luter; Dethan, Agustinus Agung (Lembaga Dongan Dosen, 2024)
Beef cattle fattening at Solidarity Cooperative Oesao Branch faces several challenges that hinder efficiency and productivity, including limited capital, feed management, health care, and waste management. The cattle paronisation programme provided by the cooperative offers loans under certain conditions to assist farmers in overcoming the problems faced. However, the current rearing system leads to longer fattening duration and increased production costs. The Community Service activity aims to identify and overcome the problems faced by farmers by offering solutions based on counselling, training and technology transfer for farmers. Activity methods include: counselling, discussion, training, as well as monitoring and mentoring the results of socialisation of activities. The results of this activity increased the knowledge of farmers of partner group members about mature business planning to support efficient and effective management of paron cattle; increased knowledge of farmers of partner group members about proper housing management to support the health and performance of cattle production, increased knowledge of farmers about feeding management according to the needs of the amount and nutrition of animal feed, an increase in farmers' understanding of cattle marketing management to increase their income and increased knowledge of partner farmers about the importance of calculating profits in the cattle business so that it is necessary to record all expenses and receipts as well as understanding knowledge about feed processing.